Pengaruh Prinsip-Prinsip Good Corporate Governance pada Kinerja Keuangan Lembaga Perkreditan Desa - Dharma Suputra, I Dewa Gede; Hendrayanti, Ni Luh Putu (E-Jurnal Akuntansi, 2020)
This research was conducted at the Village Credit Institution (LPD) in North Kuta, Kuta and South Kuta Districts. The number of samples taken was 85 people with the Head and the LPD Supervisory Board as respondents, using non-probability sampling methods, especially saturated sampling. Data collection is done by questionnaire technique. The analysis technique used is multiple linear regression. Based on the results of the analysis it was found that transparency, accountability, responsibility, independence and fairness had a significant positive effect on financial performance. This shows that the more transparent in presenting information, responsible for managing LPDs, complying with applicable regulations, independent and fair and fair in giving tasks, the financial performance will increase. Keywords: Financial performance; Transparency; Accountability; Responsibility; Independence; Fairness; LPD.